Return predictability of short-selling and financial distress firms: Evidence from Korean stock market - Wang, Shu Feng (Pacific Basin Finance Journal, 2023)
This paper investigates the relationship between short-selling activity and one-month ahead stock returns, with a focus on the role of distressed firms in the Korean stock market. In contrast to the U.S. market, we find that short-selling activity is concentrated on firms in the investment-grade group. Consistent with prior research, we find predictability of short-selling trading in stock returns. Moreover, we find that short-selling activity has significant role in predicting stock returns for investment-grade but not for speculative-grade group in the Korean market.
Keywords: Credit rating; Korean stock market; Short selling